PENAMBAHAN TWEEN80TM DAN ERGOSTEROL UNTUK MENGATASI OSMOTIC SHOCK DAN KERUSAKAN MEMBRAN SEL DALAM PROSES FEREMENTASI BIOETANOL DARI NIRA NIPAH KENTAL - Delvi Andika; Fajar Restuhadi; Chairul ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study was conducted to determine the optimization of bioethanol production by fermentation techniques VHGF with free cell system to see the effect of combined treatment of unsaturated lipid concentrations (0.2% Tween80. And Ergoterol) the increase in bioethanol. This research was carried out experiments with four treatments and measurements in duplicate. The combination of ergosterol levels namely E0 (0 mg / l), E1 (18 mg / l), E2 (24 mg / l) and E3 (30 mg / l). Observations were made every 24 hours; include sugar, ethanol, cell number, and pH. Data were analyzed descriptively by using a tabular or graphical. The best treatment is a combination of E1 (0.2% Tween80 and ergosterol 18 mg / l), which produces the largest ethanol 17.57%. Keywords: Nira Nipah, Tween80TM, Ergosterol, Batch, Bioethanol, Fermentation Media Chowder